2007
DOI: 10.1074/jbc.m700841200
|View full text |Cite
|
Sign up to set email alerts
|

C1 Inhibitor Serpin Domain Structure Reveals the Likely Mechanism of Heparin Potentiation and Conformational Disease

Abstract: C1 inhibitor, a member of the serpin family, is a major downregulator of inflammatory processes in blood. Genetic deficiency of C1 inhibitor results in hereditary angioedema, a dominantly inheritable, potentially lethal disease. Here we report the first crystal structure of the serpin domain of human C1 inhibitor, representing a previously unreported latent form, which explains functional consequences of several naturally occurring mutations, two of which are discussed in detail. The presented structure displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 59 publications
9
65
0
Order By: Relevance
“…The expression yields ranged from 3-10 mg/l and, therefore, were comparable to that reported previously for the production of full-length C1 inhibitor using the same expression system (16). In keeping with the report by Wolff et al (16) and in contrast with the highly heterogeneous material produced in P. pastoris (12,19), the C1 inhibitor serpin domain expressed in the current study was homogeneous in terms of size, as shown by SDS-PAGE and MALDI mass spectrometry analyses, indicating relative homogeneity of the N-linked oligosaccharides. In this regard, the mass spectrometry analyses performed on the recombinant proteins are consistent with the occurrence of short, oligomannose carbohydrates comprising two N-acetylglucosamine residues and three to four mannose residues (calculated mass = 893-1055), in keeping with previous analyses (16).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The expression yields ranged from 3-10 mg/l and, therefore, were comparable to that reported previously for the production of full-length C1 inhibitor using the same expression system (16). In keeping with the report by Wolff et al (16) and in contrast with the highly heterogeneous material produced in P. pastoris (12,19), the C1 inhibitor serpin domain expressed in the current study was homogeneous in terms of size, as shown by SDS-PAGE and MALDI mass spectrometry analyses, indicating relative homogeneity of the N-linked oligosaccharides. In this regard, the mass spectrometry analyses performed on the recombinant proteins are consistent with the occurrence of short, oligomannose carbohydrates comprising two N-acetylglucosamine residues and three to four mannose residues (calculated mass = 893-1055), in keeping with previous analyses (16).…”
Section: Discussionsupporting
confidence: 67%
“…This value is slightly higher but comparable to those measured for the interaction of heparin with C1 inhibitor and C1s. Therefore, this result seems to be consistent with a "sandwich" mechanism rather than with a "bridging" mechanism (19); in the latter case, the oligomer size necessary to achieve half-maximal potentiation would be expected to be much higher. Similar potentiation curves were obtained using C1inhD97 instead of full-length C1 inhibitor (data not shown).…”
Section: Interaction With Heparinsupporting
confidence: 67%
See 2 more Smart Citations
“…C1-inh is a serpin (serine protease inhibitor) that makes a covalent complex with the protease molecule, distorting its structure and preventing cleavage of further substrate molecules (Beinrohr et al, 2007). We wanted to unambiguously exclude the possibility that the C1-inh mediated inhibition of the cell activating ability of MASP-1 is due to steric reasons; i.e.…”
Section: Discussionmentioning
confidence: 99%